Syntaxonomy, diversity and distribution of the vegetation of rock crevices, clefts and ledges in the colline and montane belts of Central Pamir-Alai and Western Tian Shan Mts (Middle Asia) - Nowak, Arkadiusz; Świerszcz, Sebastian; Nowak, Sylwia; Nobis, Agnieszka; Klichowska, Ewelina; Nobis, Marcin (Plant biosystems)
Mountain areas are very often considered to be biodiversity hotspots. Rocks are one of the most unique habitats and serve as a suitable biotope for many endemic and specialized plant species. Here we present the results of the vegetation studies conducted in central and eastern Pamir-Alai and the south-western Tian Shan mountains in 2013‒2019. Based on 334 phytosociological relevés we propose a synopsis of the rock communities of the montane and colline zones of eastern Middle Asia. As a result of our research, we distinguish 17 communities defined into five groups of petrophytic vegetation within the Caricion koshewnikowii alliance. We describe 11 new associations: Feruletum bucharicae, Scrophularietum glabellae, Asperulo albiflorae-Kafirniganietum hissaricae, Scutellarietum immaculatae, Campanuletum eugeniae, Silenetum kuschakewiczii, Rosularietum platyphyllae, Spireaetum pilosae, Silenetum lithophilae, Campanuletum albertii, and Rhinactinidietum limoniifoliae. Distinctiveness of environmental conditions together with the species composition of the phytocoenoses within the montane and colline belts of eastern Middle and Central Asia make the investigated vegetation among those with the highest specific diversity and richness of endemisms in the whole area. The main factors that determine the species composition of the investigated vegetation seem to be phytogeography, altitude, bedrock type, and exposition. Supplemental data for this article is available online at